Multiculturalism and Interculturalism as the Points of Reference for Teaching Competencies - Szerląg, Alicja (Acta Paedagogica Vilnensia, 2017)
Multiculturalism is a cultural category typical of the present times, locating the individual within the borderlands of cultures, i.e., in a place of experiencing not only one’s own self and own culture, but also the relation with Others and their cultures. Thus, this is a place of constant choices and cultural identifications, conceptualizing the process of developing multidimensional cultural identity and establishing a community in these cultural borderlands. The frontier character of an individual’s functioning exposes the category of interculturalism by entailing its typical competencies, i.e., social (personal, interpersonal, cross-cultural) and civic ones. The acquisition of such features by the young generation is subject to intentional educational influences, carried out, among others, within the framework of the cross-cultural education. Therefore, the importance is assigned to the role of the teacher and his/her professional competencies (personal, interpretative-communicative, creative-critical, cooperation, axiological, teleological and executive), shaped within academic education.